MENDIAGNOSA PENYEBAB PENYAKIT STROKE PADA PASIEN MENGGUNAKAN METODE BACKWARD CHAINING - Alfarizki Gunadi, Iqbal; Alfa Rizi, Muhammad; Dharma Putra, Aditya; Azun Manalu, Ali; Rosyani, Perani (BISIK : Jurnal Ilmu Komputer, Hukum, Kesehatan dan Sosial Humaniora, 2023)
Backward chaining is a way to find the appropriate object by using the information contained in one of the methods used in the inference engine. The inference engine is a method used to diagnose 9 diseases that have the potential to cause stroke by completing the rules that will be used in making a decision tree. In this decision tree, it will be traced using a breadth-first search technique where the nodes on the symptoms of the disease indicated by the patient will be connected with arcs (arcs) by tracing all the existing nodes so that the desired conclusion is obtained. The data used to build the knowledge base is data collected by carrying out direct observations in the recovery rehabilitation clinic for stroke sufferers, conducting interviews with several doctors of internal medicine and neurology. In addition, the author also prepared a questionnaire that was given to stroke sufferers for them to fill out. With the use of this method, it is hoped that it can help in carrying out an analysis to diagnose in the form of information on diseases that cause stroke so that prevention and treatment can be immediately carried out.